The determinants of employment status in Egypt - Assaad, Ragui; El-Hamidi, Fatma; Ahmed, Akhter (International Food Policy Research Institute, 2000)
Egyptian labor market is moving from a period of high overall unemployment to one where unemployment is increasingly concentrated among specific groups whose access to the private-sector labor market is limited. Educated young women are more adversely affected than their male counterparts by the transition to a private-sector-led economy. There is no systematic link between youth unemployment among new entrants and poverty unless it is the head of the household who is unemployed. An economic policy environment that is favorable for labor-intensive, export-oriented industries would help absorb the new entrants into the labor market, and the prospect is particularly good for young female workers. Policymakers should consider a reduction in the female-specific employer mandates (such as the existing provision for a generous maternity leave) that raise the cost of hiring women.